Designing a Model for the Selection of Branch Managers at Bank Melli Iran - Nejd Ghasem Bonab, Ahad; Beikzad, Jafar; Mojallal, Mohammad Ali (Management Strategies and Engineering Sciences, 2025)
This study was conducted with the aim of designing a model for the selection of branch managers at Bank Melli Iran. The strategy of this research is qualitative and based on the meta-synthesis approach. The statistical population of the study consists of two parts: documents, articles, theses, books, and scientific records related to the research topic from the years 2011–2024 (Gregorian calendar), and interviews with three groups—academic experts, senior professionals, and executive managers of Bank Melli Iran. Sampling of scientific sources was performed using a purposive method aligned with the meta-synthesis approach. Additionally, purposive and snowball sampling methods were used to identify research participants, continuing until theoretical data saturation was reached. Ultimately, 16 individuals were selected as the final sample. Data were analyzed using the seven-step approach by Sandelowski et al. (2007). Based on the data analysis, the model for selecting branch managers at Bank Melli Iran was designed in the form of 6 main categories, 17 subcategories, and 81 concepts. According to the findings of this study, it can be concluded that the selection and appointment of branch managers at Bank Melli Iran requires comprehensive and systematic attention to a combination of professional competencies, behavioral capabilities, ethical characteristics, managerial skills, and strategic insight.